The oldest known lepidosaur and origins of lepidosaur feeding adaptations - Daniel Marke; David I. Whiteside; Thitiwoot Sethapanichsakul; Robert A. Coram; Vincent Fernandez; Alexander Liptak; Elis Newham; Michael J. Benton (Nature, 2025)
Abstract The Lepidosauria is the most species-rich group of land-dwelling vertebrates. The group includes around 12,000 species of lizards and snakes (Squamata) and one species of Rhynchocephalia, the tuatara Sphenodon punctatus from New Zealand 1 . Squamates owe their success to their generally small size, but also to their highly mobile skull that enables them to manipulate large prey. These key features of lizard and snake skulls are not seen in Sphenodon , which makes it important to understand the nature of their common ancestor. Lepidosaurs originated in the Triassic 252–201 million years ago, but confusion has arisen because of incomplete fossils, many of which are generalized lepidosauromorphs, neither squamates nor rhynchocephalians 2–5 . Here we report a reasonably complete skull and skeleton of a definitive rhynchocephalian from the Middle Triassic (Anisian) Helsby Sandstone Formation of Devon, UK that is around 3–7 million years older than the oldest currently known lepidosaur. The new species shows, as predicted, a non-mobile skull but an open lower temporal bar and no large palatine teeth, and it seems to have been a specialized feeder on insects. This specimen helps us understand the initial diversification of Lepidosauria as part of the Triassic Revolution, when modern-style terrestrial ecosystems emerged.